Translingual Discrimination: Skilled Transnational Migrants in the Labour Market of Australia - Dovchin, Sender; Dryden, Stephanie (2022)
Drawing on linguistic ethnographic data, this study examines the language-based discriminatory experiences of skilled transnational migrants in the labour market of Australia. Moving beyond two main concepts of 'interlingual' and 'intra-lingual' discrimination in applied linguistics, this article points out the concept of 'translingual discrimination', which refers to inequality based on transnational identities' specific linguistic repertoires and backgrounds that are substantiated by the national order of things. Translingual discrimination adds intensity to transnational processes, with the skilled migrants showing particular potential for exclusion regarding two factors: translingual 'name discrimination' and 'English discrimination'. 'Translingual name discrimination' is a homogenous form of 'name' policing, evident in multiple examples where the skilled transnational migrants' job applications are often largely rejected on the grounds of their 'birth name' written on their curriculum vitae. 'Translingual English discrimination' is another common form of discrimination, where the skilled transnational migrants become subject to discrimination based on their English proficiency and their overall language skills, leading to 'the paradoxes of migration' - discrepancies between the imagination and the reality - where they fall from 'hero to zero' in the host society.